Infant Feeding Practices of HIV Positive Mothers and Its Association with Counseling and HIV Disclosure Status in Ethiopia: A Systematic Review and Meta-Analysis - Getaneh Mulualem Belay; Chalachew Adugna Wubneh (AIDS Research and Treatment)
Introduction. Breastfeeding is the ideal food source for all newborns globally. However, in the era of Human Immune Deficiency Virus (HIV) infection, feeding practice is a challenge due to mother-to-child HIV transmission. Therefore, this systematic review and meta-analysis aimed to estimate the national prevalence of exclusive breastfeeding and mixed feeding practices among HIV positive mothers and its association with counseling and HIV disclosure status to the spouse in Ethiopia. Methods. We searched all available articles from the electronic databases including PubMed, EMBASE, Google Scholar, and the Web of Science. Moreover, reference lists of the included studies and the Ethiopian institutional research repositories were used. Searching of articles was limited to the studies conducted in Ethiopia and published in English language. We have included observational studies including cohort, cross-sectional, and case-control studies. The weighted inverse variance random effects model was used. The overall variations between studies were checked through heterogeneity test (I2). Subgroup analysis by region was conducted. To assess the quality of the study, the Joanna Briggs Institute (JBI) quality appraisal criteria were employed. Publication bias was checked with the funnel plot and Egger’s regression test. Result. A total of 18 studies with 4,844 participants were included in this study. The national pooled prevalence of exclusive breastfeeding and mixed feeding practices among HIV positive mothers were 63.43% (95% CI: 48.19, 78.68) and 23.11% (95% CI: 10.10, 36.13), respectively. In the subgroup analysis, the highest prevalence of exclusive breastfeeding practice was observed in Tigray (90.12%) and the lowest in Addis Ababa (41.92%). Counseling on feeding option with an odds ratio of 4.32 (95% CI: 2.75, 6.77) and HIV disclosure status to the spouse with an odds ratio of 6.05 (95% CI: 3.03, 12.06) were significantly associated with exclusive breast feedings practices. Conclusion. Most mothers report exclusive breastfeeding, but there are still almost a quarter of mothers who mix feed. Counseling on feeding options and HIV disclosure status to the spouse should be improved.